O3-Induced Priming Defense Associated With the Abscisic Acid Signaling Pathway Enhances Plant Resistance to Bemisia tabaci - Guo, Honggang; Sun, Yucheng; Yan, Hongyu; Li, Chuanyou; Ge, Feng (Frontiers in Plant Science, 2020)
Elevated ozone (O3) modulates the phytohormone signals, which subsequently alters the interaction between plant and herbivorous insect. It has been reported that elevated O3 activates the plant abscisic acid (ABA) signaling pathway, but its cascading effect on the performance of herbivorous insects remains unclear. Here, we used the ABA-deficient tomato mutant notabilis (not) and its wild type, Ailsa Craig (AC), to determine the role of ABA signaling in mediating the effects of elevated O3 on Bemisia tabaci in field open-top chambers (OTCs). Our results showed that the population abundance and the total phloem feeding duration of B. tabaci were decreased by O3 exposure in AC plants compared with not plants. Moreover, elevated O3 and B. tabaci infestation activated ABA signaling pathway and enhanced callose deposition in AC plants but had little effect on those in not plants. The exogenous application of a callose synthesis inhibitor (2-DDG) neutralized O3-induced resistance to B. tabaci, and the application of ABA enhanced callose deposition and exacerbated the negative effects of elevated O3 on B. tabaci. However, the application of 2-DDG counteracted the negative effects of O3 exposure on B. tabaci in ABA-treated AC plants. Collectively, this study revealed that callose deposition, which relied on the ABA signaling pathway, was an effective O3-induced priming defense of tomato plants against B. tabaci infestation.